SIMULASI SPASIAL BERBASIS SISTEM INFORMASI GEOGRAFI DAN CELLULAR AUTOMATA UNTUK PEMODELAN PERUBAHAN PENGGUNAAN LAHAN DI DAERAH PINGGIRAN KOTA YOGYAKARTA - Bowo Susilo (Bumi Lestari Journal of Environment, 2013)
AbstractLand use change is one of phenomena which have relation to various environmental issues.Global warming, loss of biodiversity and impact to human life are main issues related toland use change. Those issues have been drive international organizations to developparticular program to study land use change. One of the well known programs is Land Use/Cover Change (LUCC).Working group of LUCC suggested three core subject of researchrelated to land use change. Those are situation assessment, modeling and projecting andconceptual scaling.This research aimed to modeling dynamic of land use change based on spatial simulation.Integration of cellular automata and geographic information system were used to performspatial simulation. Modeling of land use dynamic was focused on conversion from agricultureland to non agriculture land. Three sub districts which are situated at urban fringe ofYogyakarta had been selected as research area. Those three sub districts were Depok,Mlati and Gamping.Time series of land use maps comprising year 1982, 1992 and 2000 as well as populationdata were used to generate input of spatial simulation. Several maps which denote qualityof land were used to develop transition rule. Results of simulation were spatial predictionof land use change for year 2001 toward 2007. It was then validated using land use 2007as reference. Validation test show that predicted and actual condition have fair agreement.